Unity is Strength. A history of the Australian Labor Party and the Trades and Labor Council in Western Australia, 1899-1999 - Oliver, Bobbie (API Network, Australia Research Institute, Curtin University, 2003)
In April 1899, 28 men met in Coolgardie on the Eastern Goldfields to hold Western Australia's first Trades Union Council. It was the genesis of an organised labour movement that, by 1907 was to span the vast State. For 60 years the Australian Labor Party in Western Australia was unique, comprising political and industrial wings in one united body, thus exemplifying the motto, Unity is Strength. Changing circumstances, including the Party split in the 1950s, however, revealed the need to change the existing structure and an independent Trades and Labor Council formed in 1963. During the ALP's first century, Labor governments held in office in the State for a total of 45 years, leaving an impressive record of social and political reform despite always having to contend with a non-Labor majority in the Legislative Council.Interwoven with the stories of Premiers, Party and union leaders, however, in this Centenary History of the Australian Labor Party (WA), Bobbie Oliver includes the contributions of bush organisers and party workers. Drawing on a vast body of archival material, Dr Oliver relates the slow and often unseen progress of women and minority groups in achieving influence in the Party or the industrial organization. Together with the well publicized struggles and triumphs of the twentieth century including: the 40-hour week, the right of free speech and assembly, health and safety in the workplace, an equitable voting system, are Party splits over conscription in 1916 and in the 1950s creating the Democratic Labor Party; the rise of factionalism, disputes between the Party and the TLC, and 'WA Inc'.In the late 1990s, in the context of hostile 'Third Wave' industrial legislation and the 'War on the Wharves', the ALP and the Trades and Labor Council found new truth in the old motto, Unity is Strength.